Patient, parental and multi-disciplinary team rationale for non-implantation following the paediatric cochlear implantation assessment. (4th May 2022) - Hall, Andrew; McClenaghan, Fiona; Nash, Robert; Shaida, Azhar
Abstract : Objectives: To assess paediatric patients referred to the cochlear implant team, who despite undergoing the assessment, did not receive cochlear implantation. To identify the underlying reasons for this. Methods: A retrospective case-note review of patients was assessed from June 2014 to June 2019 at two separate London teaching hospitals with paediatric cochlear implantation programmes. Results: A total of 921 paediatric patients were assessed during the study period across both institutions. And, 196 (21%) did not proceed with the surgery. The decision not to undergo surgery was primarily parental/patient-directed in 114 (61%) and cochlear implant team-directed in 74 (39%). In total, eight (4%) patients exited the programme without a documented reason. Discussion: A myriad of factors influenced the decision-making process for clinicians, patients and parents. The most cited parental/patient rationale against implantation was the wish to continue current means of communication 40 (35%), followed by concern regarding the risks of surgery 18 (15.8%) and the wish to allow the patient to make future decisions independently in view of the future technology 7 (6.1%). Cochlear implant team-directed decisions were largely due to being outside of the NICE criteria 27 (36.5%) or the risks of general anaesthesia 19 (25.7%) in addition to communication concerns 11 (14.9%). Conclusion: Decision-making in cochlear implantation should not be underestimated. Extensive discussion and exploration of options with the multi-disciplinary team can aid decision-making, but the timescale and appreciation of the consequences of the decision inevitably lead to pressure. Exploration of reasons for non-implantation emphasises the importance of a multi-professional approach to manage these patients.